Ergodesign and information architecture: working with user - Zilse, Renata (InfoDesign, 2007)
AGNER, Luiz. Ergodesign e arquitetura da informação: trabalhando com o usuário. Rio de Janeiro: Quartet, 2006. 173p. [ISBN 85-85696-80-X] Ergodesign and information architecture approaches user centered design issues from different viewpoints: the clients, the designers, system analysts and information architects. The book is addressed to novice audiences (those interested in working in this field), and focusing on them it develops the content in a simple manner and with colloquial language. ´If, as the author Luiz Agner says, nowadays crisis regards in fact “how to transform information in knowledge”, he started to fight the crisis when he decided to produce a goodhumoured and understandable book for all interested in this theme’. [ANAMARIA DE MORAES, 2006]